2010
DOI: 10.1371/journal.pone.0009698
|View full text |Cite
|
Sign up to set email alerts
|

Anti Transglutaminase Antibodies Cause Ataxia in Mice

Abstract: BackgroundCeliac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one.MethodsWe analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 41 publications
2
76
0
Order By: Relevance
“…Mutations of the TGM6 gene may lead to functional impairment and finally neuronal loss in these brain regions as SCA development progresses. An in vivo study has shown that intraventricular injection of anti-TG2/3/6 cross-reactive antibody provoked ataxia in mice (Boscolo et al, 2010). Taken together, the high distribution density of TG6-positive neurons in the extrapyramidal system supports the hypothesis that TGM6 is the causative gene in the development of SCA 35 (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…Mutations of the TGM6 gene may lead to functional impairment and finally neuronal loss in these brain regions as SCA development progresses. An in vivo study has shown that intraventricular injection of anti-TG2/3/6 cross-reactive antibody provoked ataxia in mice (Boscolo et al, 2010). Taken together, the high distribution density of TG6-positive neurons in the extrapyramidal system supports the hypothesis that TGM6 is the causative gene in the development of SCA 35 (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…All three TG isozymes (TG2, TG3, TG6) for which autoantibodies have been described, can form thioester-linked complexes with gluten peptides which are thought to be responsible for the B cell response to TG isozymes [14,18]. Pathogenicity of such circulating anti-TG antibodies in terms of leading to extraintestinal disease has been demonstrated in animal models [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…When using sera from patients with GA there is evidence of additional antibodies targeting Purkinje cell epitopes since elimination of AGA alone is not sufficient to eliminate such reactivity. There is evidence that the additional antibodies that may be causing such reactivity, are antibodies against one or more transglutaminase isoenzymes (TG2, TG3, TG6) (Boscolo et al, 2010). TG2 belongs to a family of enzymes that covalently crosslink or modify proteins through transamidation, deamidation or esterification of a peptidebound glutamine residue (Aeschlimann and Thomazy, 2000).…”
Section: Pathogenesismentioning
confidence: 99%
“…A common problem in such studies is to be able to demonstrate whether it is these specific antibodies or other autoantibodies in the IgG-fraction of patient sera that cause neuronal damage. Using a mouse model we have recently shown that serum from GA patients as well as clonal monovalent anti-TG immunoglobulins derived using phage display, cause ataxia when injected intraventricularly in mice (Boscolo et al, 2010). The fact that not only Ig fractions but also monospecific scFv's mediate functional deficits shows that there is no requirement for complement activation or for the engagement of Fc receptors on Fc-receptor bearing cells in the brain.…”
Section: Pathogenesismentioning
confidence: 99%